Jejuelen.com : Digitalisasi Pasar Produk Potensial Desa Karangmelok, Kecamatan Tamanan Kabupaten Bondowoso Guna Mewujudkan Desa Kreatif Mandiri - Adi Putra, Januar; Venantya Asmandani; Fahrobby Adnan (Jurnal Mitra Pengabdian Farmasi, 2022)
Karangmelok Village, Tamanan District, Bondowoso Regency has a lot of potential products that can be developed to lift the economy of the population, but these are not utilized properly. The lack of utilization of technological developments is one of the main causes of the lack of recognition of potential products in Karangmelok Village, Tamanan District, Bondowoso Regency. With the ineffective use of technology, the marketing carried out is not optimal and results in small income received. Based on data compiled by the Institute for Research and Community Service (LP2M) of the University of Jember (UNEJ), the main problems that have been mentioned occur in most MSMEs in Karangmelok Village, Tamanan District. Based on the problems above, it is proposed that service activities using technology can accommodate all MSMEs in Karangmelok Village, so that they can realize the village's dream, which is to become an MANDIRI CREATIVE VILLAGE. Based on the results of the service activities that have been carried out, it can be concluded that the application that has been built is able to help and support the improvement of the sales and administration processes of partners, especially in the marketing module developed in this phase. The ability of this application cannot be separated from the requirements gathering process which has been adapted to the needs of users in the field, because each user has different needs. As well as in presenting the data according to the real condition data in the field. So that the information generated by the application has a fairly high data accuracy with the reality on the ground.